Analisis Sistem Antrian di Indomaret Fresh Bitung dengan Pendekatan Teori Antrian dan Simulasi - Nanda Dwi Putra Purba; Sylvia Sylvia; Rifqi Bilal Kumara; Yoga Rendika; Yoga Putranto; Nuryudha Darmawan (Universitas Pelita Harapan, 2026)
This study analyzes the performance of the cashier queueing system at Indomaret Fresh Bitung using observational data on inter-arrival times and service times, integrated with simulation modeling. The data collected indicate that customer inter-arrival times follow an exponential distribution. The analysis demonstrates that shorter inter-arrival times substantially increase waiting times and server utilization. During peak hours, an average inter-arrival time of 1.21 minutes results in an average waiting time of 0.769 minutes and a server utilization rate of 60%, indicating that the cashier operates near maximum capacity. In contrast, during non-peak hours, a longer average inter-arrival time of 1.832 minutes reduces system workload, leading to a shorter average waiting time of 0.341 minutes and increasing the probability of server idleness to 62.5%. Combined simulation results reveal a relatively balanced operational condition with an overall utilization level of 50%. Overall, the findings confirm that shorter inter-arrival times increase the likelihood of queue formation; therefore, optimal resource allocation during peak periods is necessary to maintain service efficiency.